2014
DOI: 10.5539/jgg.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Geovisualizing Topographical Data Using Geographic Information System (GIS)

Abstract:  Indonesia lied among the three of world major plates so that several districts along the southern coast of Java Island were vulnerabled to the tsunami including Lumajang. South coast of Lumajang had high population density and settlements and high levels of government and economic activity. Therefore, it is necessary to know the level of insecurity and vulnerability to the tsunami in order to be utilized as input of mitigation data for the preparation of regional spatial plans (RTRW) based on tsunami risk le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The building of dams on the Tigris and the Euphrates and their tributaries by countries that originate or pass from them, such as Turkey and Syria, global climate change, and mismanagement of these resources are reasons leading to the scarcity of water in Iraq by the year 2040 [1]. Geographic information systems (GIS) are used to classify and analyze information and store it in databases [2]. The methods of obtaining data using GIS allowed geographers, engineers, and those interested in accessing for any part of the world, even those that are difficult to reach using traditional methods [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The building of dams on the Tigris and the Euphrates and their tributaries by countries that originate or pass from them, such as Turkey and Syria, global climate change, and mismanagement of these resources are reasons leading to the scarcity of water in Iraq by the year 2040 [1]. Geographic information systems (GIS) are used to classify and analyze information and store it in databases [2]. The methods of obtaining data using GIS allowed geographers, engineers, and those interested in accessing for any part of the world, even those that are difficult to reach using traditional methods [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Geographic information systems (GIS) are used to classify and analyze information and store it in databases [2]. The methods of obtaining data using GIS allowed geographers, engineers, and those interested in accessing for any part of the world, even those that are difficult to reach using traditional methods [3,4]. DEM is a three-dimensional representation of the earth's surface, and it is one of the easiest types of digital representation of the topography of the surface of the earth.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, studies using Remote Sensing data, Cartographic principles and Geographic Information System (GIS) in examining earth's surface spatial elements are specifically aimed at making informed decisions because the spatial outputs, mostly in the form of maps and accompanied statistics, help in resource allocation and landuse management on one hand, and policy impact analysis on the other hand (Goodchild, 1992;Ojigi, 2006;. In addition, informed decisions are useful for planning purposes in areas like topographical mapping (Ikhuoria and Ogedegbe, 1998;Soneye and Akintuyi, 2013), environmental management (Worboys, 2003), land suitability and crop production (Verhulp and Niekerk, 2017;Rilwani, 2014), topographic analysis and visualization (Yokoyama, Shirasawa and Pike, 2002;Fabiyi, Ige-Olumide and Enaruvbe, 2012;Nkeki and Asikhia, 2014), as well as urbanisation, industrialization and regional planning (Omuta, 1984;Fasona and Omojola, 2004). In other words, having reliable and up-to-date spatial data sources such as Satellite Remote Sensing, ground surveying and croudsourced mapping are regarded as fundamental to effective planning and infrastructural development (Ufuah, 2003;Bello and Ojigi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the dearth of reliable and up-to-date geographic data is a major drawback in making informed decisions as far as good governance and development are concerned in developing countries like Nigeria (Ufuah, 2003;Nkeki and Asikhia, 2014;Rilwani, Bello and Onothoja, 2015). Besides, the high temporal resolution in continuously providing multi-date satellite image data over a given geographic space is germane (Roostaei, Alavi, Nikjoo, and Valizadeh-Kamran, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation